مدى التزام بعض أصحاب المسالخ والعاملين بالاشتراطات الصحية ومعايير الجودة في المسالخ بمدينة نالوت - أ.ناجي صالح ورغ; د.ناجي الهادي أبوراس; أ.أمينة عيسى الجربى (Sharwes Scientific Journal, 2025)
This study aimed to know the extent of the commitment of slaughterhouse owners and workers to health requirements and quality standards and their impact on bacterial contamination in slaughterhouses in the city of Nalut. The experimental approach and the descriptive analytical approach were followed. 16 samples were collected from two slaughterhouses in the city, and the collected samples were divided at a rate of two samples for each of the floors, walls, knives and workers’ hands. The results showed that slaughterhouse A complies with health requirements by 37.88%, while the results showed that slaughterhouse B complies with health requirements by 30.30%, while the results of microbiological tests of the samples taken showed that the percentage of Staphylococcus aureus bacteria was 75%, 50%, 50%, 50% in the samples of floors, walls, knives and workers’ hands, respectively, while the percentage of E-Coli bacteria was 100%, 100%, 100%, 50% in the samples of floors, walls, knives and workers’ hands, respectively, while the percentage of Salmonella bacteria was 100%, 100%, 100%, 100% in the samples of floors, walls, knives and workers’ hands, respectively, The total percentage of bacterial contamination in the slaughterhouses of the city of Nalut was 81.25% which shows the extent of slaughterhouse pollution and non-compliance with health requirements and quality standards for slaughterhouses.